Evolution of the Image of St. Michael in the Art of Sevillian Masters of the Middle and the Second Half of the 17th Century - Prikladova, Maria A. (Actual Problems of Theory and History of Art, 2013)
The article is dedicated to evolution of the image of St. Michael in the art of Sevillian sculptors of the middle and the second half of the 17th c. and its differences in comparison with works of the first half of the century. It touches on works of main masters of this period, such as Juan Martínez Montañés, Pedro Roldan and Luisa Roldan.
Keywords: Spanish sculpture; Baroque; the 17th century